Solar energy demonstrator design and testing series circuit with 350 panel tilt angle in the sunrise and sunset direction - Susilo, Hendra; Mulia, Mulia; Sinurat, Fadlah K.; Supriadi, Supriadi; Suardi, Suardi (Trigin Publisher, 2024)
This research focuses on the design of a solar energy demonstrator with a 35-degree tilted panel configuration, as well as testing its performance in orientation towards sunrise and sunset in real environmental conditions. The evaluation was conducted to analyze the effect of tilt angle and orientation on the efficiency of the solar panel system. The tests were conducted for five days (October 07-12) between 8 a.m. and 4 p.m. The maximum power was achieved at 10 a.m. and 10 p.m., respectively. Maximum power was achieved from 10:00 to 12:00, with a peak of 70 watts on October 07, indicating optimal conditions for sunlight absorption. In contrast, the power generated in the morning (08.00-09.00) and afternoon (15.00-16.00) was lower, ranging from 10-30 watts, due to lower solar intensity. In terms of efficiency, the highest peak reached 50% at 10:00 to 12:00 on October 07, while in the morning and afternoon, the efficiency decreased to 10-20%. The difference between days was influenced by weather conditions, with October 07 and 08 having higher power and efficiency. This research shows the importance of tilt angle, orientation, time of day, and weather conditions in determining the optimal performance of solar panels.